The Western Denmark Heart Registry and Population-Based National Health Registries - Gyldenkerne C; Olesen KKW; Thrane PG; Hansen MK; Stødkilde-Jørgensen N; Andersen MH; Mortensen MB; Jensen JM; Nørgaard BL; Sørensen HT; Maeng M (Clinical Epidemiology, 2024)
Christine Gyldenkerne,1,2 Kevin Kris Warnakula Olesen,1 Pernille Gro Thrane,1 Malene Kærslund Hansen,1 Nina Stødkilde-Jørgensen,1 Malene Højgaard Andersen,1 Martin Bødtker Mortensen,1,3 Jesper Møller Jensen,1 Bjarne Linde Nørgaard,1,4 Henrik Toft Sørensen,2 Michael Maeng1,4 1Department of Cardiology, Aarhus University Hospital, Aarhus, Denmark; 2Department of Clinical Epidemiology, Aarhus University and Aarhus University Hospital, Aarhus, Denmark; 3Ciccarone Center for the Prevention of Cardiovascular Disease, Johns Hopkins University School of Medicine, Baltimore, Maryland, USA; 4Department of Clinical Medicine, Aarhus University Hospital, Aarhus, DenmarkCorrespondence: Christine Gyldenkerne, Department of Cardiology, Aarhus University Hospital, Palle Juul-Jensens Boulevard 99, Aarhus N, 8200, Denmark, Tel +4560949704, Email chgyld@clin.au.dkAbstract: The Western Denmark Heart Registry (WDHR) is a semi-national, multicenter-based clinical registry with unique potential for cardiovascular research. The registry has provided detailed prospectively registered information on patient and procedure characteristics since 1999. WDHR data can be linked to additional data in other healthcare registries in Denmark. Therefore, the WDHR is a valuable data resource for cardiovascular research, providing a foundation for numerous research projects and publications. This review describes three currently available cohorts from the WDHR containing individual-level information on: i) 200,647 first-time coronary angiographies from 2003 to 2021, ii) 88,630 first-time percutaneous coronary interventions from 1999 to 2022, and iii) 85,512 first-time coronary computed tomography angiographies from 2008 to 2021. Furthermore, we describe other frequently cross-linked Danish healthcare registries containing information on various patient characteristics and outcomes, such as vital status, cause of death, hospitalizations, medications, and laboratory test results. The comprehensive overview of these cohorts aims to assist researchers, collaborators, and other interested parties in understanding the scope and potential applications of the available data. All cohorts are regularly updated, thereby supporting continuing research on cardiovascular clinical practice and prognosis in Denmark.Keywords: epidemiology, cardiovascular disease, cohort, coronary angiography, percutaneous coronary intervention, computed tomography angiography